Improving Mother’s Knowledge in Early Detection of Pregnancy and Childbirth Complication - Elmeida, Ika Fitria; Purwaningsih, Dewi; Risneni, Risneni; Suja, Monica Dara Delia (CV Media Inti Teknologi, 2023)
Pregnancy and childbirth complications and high risks, which are estimated to occur in 15–20% of pregnant women, are not all detected early. For those detected, not all of them have been handled in a timely and adequate manner. In one of the provinces in Indonesia, namely Lampung, there are still many women giving birth at home. Research results in the form of population-based information about birth complications in mothers must rely on reporting about mothers' experiences through interviews. The Community Health Center has carried out health promotion activities both periodically and incidentally about the health of mothers and babies. However, it is very unfortunate that people do not really understand the danger signs and how to detect early labor, so treatment is still too late. The targets for this activity were 30 pregnant and breastfeeding mothers who came to Posyandu. The types of activities carried out include providing education about recognizing the danger signs of pregnancy and childbirth and using the IKA-LIN booklet as an instrument for detecting childbirth complications. All community service participants were given a pre-test, followed by a presentation regarding the danger signs of pregnancy, after which booklets were given to all participants, and the final stage was the post-test. The final session also included questions and answers regarding the mother's experience during childbirth. There was an increase in mothers' knowledge based on the results of the pre-test and post-test.